1998
DOI: 10.1021/ic9715207
|View full text |Cite
|
Sign up to set email alerts
|

Ground State and Excited Stated Properties of Hexaamminechromium(III) Ion:  A Density Functional Study

Abstract: The electronic structure of the ground and lowest excited states of the hexaamminechromium(III) ion [Cr(NH(3))(6)](3+) has been investigated through density functional theory. The geometry of the (4)A(2g) ground state and of the (4)T(2g) excited state are optimized. The latter is relaxed along an e(g) Jahn-Teller coordinate. The experimentally known geometry distortion, i.e., an axial compression and an equatorial elongation, together with the corresponding energy gain is well reproduced by our calculations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Neither approach gave particularly good absolute results both underestimating transition energies by between 3000 to 7000 cm À1 . However, the errors are comparable to those reported for other TM complexes 44,64,[70][71][72][73][74] and it may be too much to expect present methodology to be more accurate. Presumably, the fault lies with the currently available functionals.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Neither approach gave particularly good absolute results both underestimating transition energies by between 3000 to 7000 cm À1 . However, the errors are comparable to those reported for other TM complexes 44,64,[70][71][72][73][74] and it may be too much to expect present methodology to be more accurate. Presumably, the fault lies with the currently available functionals.…”
Section: Discussionsupporting
confidence: 78%
“…Ziegler et al 62 described an approximate method for obtaining multiplet energies by computing the energies of suitable determinants. The method has been extended by Daul 43 and is reasonably accurate 63,64 but limited in that if there are two or more states with identical spatial and spin properties, it cannot resolve the possible configurational mixing which may exist. However, this issue has been resolved, at least in principle, with the advent of time dependent DFT (TDDFT).…”
Section: Excited D Statesmentioning
confidence: 99%
“…All calculations described in this work were performed on Linuxbased Pentium III 600 MHz computers with the Amsterdam Density Functional (ADF) program, version ADF2000, 32 developed by Baerends et al 33 All calculations employed the local density approximation (LDA) to the exchange potential, 34 and the correlation potential of Vosko, Wilk, and Nusair. 35 Previous studies 13,[36][37][38][39][40][41][42][43] and our own ongoing investigations 44 have shown that, for several classes of inorgranic compounds but particularly for structural features of anionic metal-containing complexes, 13,42,43 Basis sets for all atoms were of triple-ζ quality with Slater-type orbitals. Electrons in orbitals up to and including 2p {Cl, V}, 3d {Nb}, and 4d {Ta} were treated in accordance with the frozencore approximation.…”
Section: Computational Detailsmentioning
confidence: 96%
“…Another significant calculation was of the spin-orbit interaction between the 4 E g state and the upper 2 B 1g component of the 2 E g state, which conferred 3.4% t 2g 2 e g 1 character upon the latter. Recently another density functional calculation on this molecule has appeared, 154 and in this work the geometry was allowed to optimize. The bond lengths, the sequence of d-d excitation energies, and the tetragonal distortion of the 4 T 2g excited state were well reproduced, but the calculated transition energies and vibrational frequencies differed significantly from the experimental values.…”
Section: Theoretical Studiesmentioning
confidence: 99%